Identifying priority watersheds to mitigate flood and drought impacts by novel conjunctive water use management - Pavelic, Paul; Brindha, Karthikeyan (Springer, 2016)
Deficit irrigation could be considered as one potential option to improve water productivity and obtain some level of assured income under water scarcity and drought conditions in Central Asia. This article investigates water productivity and economic returns to two varieties of potato crop under four different soilmoisture regimes in Uzbekistan. Results suggest that deficit irrigation may not be considered as an option to improve water productivity of potato crop, particularly when the deficit is high. However, deficit irrigation options could be still considered as a viable option to maintain food security and some assured farm income even under extreme drought conditions.